(untitled) (Global Journals of Research in Engineering, 2022)
The healthcare delivery sector in the United States is the largest in the world It consumes over 1 6 of the Gross Domestic Product of the nation the largest such slice of an economy among all developed countries The federal and state governments account for about half of the national expenditures in this sector The complexity and the magnitude of the healthcare sector impose considerable challenges on the federal government particularly with regard to the role played by knowledge management systems KMS necessary for the effective discharge of the federal healthcare functions The federal involvement in the sector ranges from a vast regulatory apparatus to the massive funding of care through Medicare and Medicaid the research monitoring and prevention of diseases and the provision of care through military departments and the Department of Veterans Affairs